Mobile Augmented Reality Application for Augmented Reality Visualization in the Educational Context - Mazzarri Rodríguez, Carlos J. (2023)
Currently, continuous technological advancements are pervasive in society, enhancing various aspects of our lives, including entertainment, information, and communication. In this context, one of the primary domains that can benefit from these advancements is education. The constant technological developments must be applied to the educational system to keep pace with changes in our lifestyle. Augmented reality (AR) is an innovative technology that allows smartphones to combine the real environment with virtual objects. Through the device's accelerometer, gyroscope, and camera, AR places 3D models on the screen based on the user's movements, creating an interactive experience. This technology has the potential to improve the learning experience in schools, making teaching more dynamic and increasing student motivation and interest in subjects such as mathematics and sciences, among others. This paper proposes the creation of a mobile application with tools that will enable not only students but also teachers to visualize and interact with any 3D model related to school subjects, enhancing the learning process and making it more engaging for them. Additionally, teachers can add all the information they deem necessary to the page of each model to describe, explain, or highlight any relevant data for their class. The primary contribution of this study is that the system allows teachers to encapsulate knowledge into an organized learning unit, improving the learning experience for students. The impact of the application on learning was assessed through surveys administered to five high school teachers in the Metropolitan Area of Lima after they had tested the application.